Research on the Influence of Surface Roughness on the Flow Field in the Cascade - Wang, Yanhua; Dai, Jun; Zhou, Shaowei; Wang, Meng; Wang, Zhongyi (Frontiers in Energy Research, 2022)
Fouling, corrosion, and icing are very common reason for increasing the roughness of the compressor blade due to the special working condition and natural environment. These changes would influence on flow field. Especially in the supersonic compressor cascade, incident wave would interact with reflected shock wave. Studies show that boundary layer conditions of the blade vary with the changing of wall roughness. It has an impact on the incident and reflected shock wave. In order to study the effect of the distribution of roughness, the effect of blade surface roughness on the suction side flow field is simulated. The results show that the flow loss is reduced with the increasing roughness at the incidence point of incident wave and the trailing edge of suction-side.